Solid pseudopapillary tumor of the pancreas: Emphasis on differential diagnosis from aggressive tumors of the pancreas - Fatma AYDINER; Hilal ERİNANÇ; Berna SAVAŞ; Esra ERDEN; Kaan KARAYALÇIN (Turkish Journal of Gastroenterology, 2019)
-